Regulatory Impact Assessment (RIA) on Grant Assistance Policy in Badung Regency - Ida Ayu Putu Sri Widnyani; I Made Sumada; Nyoman Diah Utari Dewi; I Wayan Astawa; Putu Yudi Sumertana; Ni Made Pitri Rahayu (Goodwood Publishing, 2026)
Purpose: The purpose of this study is to analyze the Regulatory Impact Assessment (RIA) of the Grant Aid Policy in Badung Regency. Research methodology: This study uses a qualitative approach with the Regulatory Impact Assessment data analysis technique. Results: The targeted outputs in this study are the analysis of the impact, costs and benefits of the Badung Regency grant aid policy which can be used as evaluation material for the government in implementing the Badung Regency grant aid policy. The policy recommendation is the second option, which is to improve the grant selection and reporting process. This option provides a balance between increasing policy effectiveness and implementation risk and supports the needs of Badung Regency to ensure more optimal and transparent policy benefits. Conclusions: The study finds that Badung Regency’s grant aid policy supports culture, welfare, and local economy, but faces issues of efficiency, dependency, and coordination. While the e-Grant system improves transparency, further refinement is needed, with priority on strengthening grant selection and reporting. Limitations: The study is limited by its qualitative RIA approach, focus on Badung Regency, and emphasis on short-term impacts, which restricts generalizability and overlooks long-term sustainability. Contributions: This research contributes by applying RIA to evaluate local grant policies, emphasizing transparency, accountability, and risk management, while offering practical recommendations for more equitable and sustainable outcomes.